Implementasi Fuzzy Logic dan Trajectory Pada Manipulator Mobile Robot Untuk Deteksi Kebocoran Gas - R Rendyansyah; Aditya Putra Perdana Prasetyo; Kemahyanto Exaudi (Universitas Syiah Kuala, 2019)
Developing technology can facilitate work activities, one of which is technology in the field of robotics. One of the purposes of creating the robot was to assist in investigating suspected targets. The target can be a gas source leak object. On the other hand, gas leaks in industrial estates have a large impact on the environment. Robots are needed to facilitate the inspection process of targets suspected of gas leakage. Robots generally have systems that are integrated with sensors as interfaces and intelligent computing. In this study mobile robots and manipulators have been designed and have the purpose of inspecting objects suspected of being gas leaks. This robot system is called a mobile robot manipulator equipped with a wireless camera for object detection, two gas sensors for aroma detection, each sensor is mounted on the end-effector manipulator and next to the camera. The methods used in robots are fuzzy logic and cubic trajectory. Fuzzy logic is used to navigate robots to objects, and cubic trajectory for navigating manipulators based on the specified route. In the experiments that have been done, the mobile robot can navigate to the target until it stops at a distance of 20cm, and the manipulator is also successful in navigating. In the testing instrument, two leaking points have been determined. Each point is tested six times. The robot succeeded in detecting gas leaks with a success rate of 91.67%, and the position of coordinates read by the manipulator can be observed through the monitor.